Desenvolvimento e caracterização de metodologia para captura deCO2 e gases precursores de efeito estufa da exaustão de motores decombustão interna por adsorção - Theles de Oliveira Costa (2015)
Arising largely from the burning of fossil fuels, carbon dioxide, CO2, and the greenhouse gases precursors, which are forming in the combustion process, must be reduced substantially in the next years. The alternative would be the capture of these gases by aluminum-silicates whether or co process to be stored in other productive sectors. This paper proposes a method for removal of CO2 and greenhouse gases precursors by adsorption, by capturing and separation of these gases from otherautomotive engine exhaust of Otto cycle internal combustion with "flex fuel" technology. The adsorbents used, natural zeolite ZN2040 and synthetic zeolite Oxan_X, were characterizing by a set of specific techniques: Fluorescence Spectrometry of Xrays, X-rays Diffraction, Thermogravimetric Analysis TGDTGDTA, Adsorption/Desorption Isotherms and Measurement by Pycnometer for water intrusion.For emissions, tests and vehicle consumption were performing in the laboratory equipped with emission chassis dynamometer, gas analyzers and an experimental apparatus for carrying out the tests in a controlled environment, as urban driving cycle FTP 75. The adsorbents have been dispose in a fixed-bed column of horizontal flow, noise damper installed in the rear of the exhaust system of the vehicle, where there is agaseous flow with average temperatures between 198 and 231 °C. The synthetic zeolite Oxan_X with better performance, unique features like moderate relationship between chemical elements Si/Al (1,6:1), high ratio Si/Fe (22,5:1) and Si/Ca (27,5:1), and a basic character with pores-basic acids conjugated. In addition to presenting a, crystalline structure similar to Faujasite has type I isotherm, with high presence of micro poreshigh surface area (506,6m²/g), total volume of pores of 0,3102 cm³/g and an average diameter of 23,6 Å. The synthetic zeolite has greater sensitivity to loss of water of hydration. Already ZN2040 with crystal structure of zeolite Clinoptilolite has high relationship between Si/Al (6:1) and moderate other metals Si/Fe and Si/Ca, around 10,5:1. With acid and low surface area (59,5 m²/g), has type IV isotherms with large presence of mesoporous with average diameter of 48 Å. Two kilograms of the synthetic Oxan_X zeolite fixed bed column, showed positive results in reducing CO2 emissions and precursor gases, especially CO, both for burning Gas 22% AEAF as fuel ethanol. Reductions were obtaining on average 2,20% of CO2 and 17,00% to the precursor gases, besides contributing in reducing the other vehicular pollutants. In the mediumterm (20-year projection), the use of fixed bed column serve can reduce, approximately, 764.000 t of CO2 and 23.300 t of CO when the vehicle is operating with Gas 22% AEAF, and 1.168.000 t of CO2 and 18.000 t of CO when the vehicle is on ethanol, considering motor vehicles 1.4 L to 2.0 L of the Brazilian fleet. Regardless of the reduction levels obtained with the method of capture, this unprecedented research paves the way for an improvement of the methodology involving new materials and newtechniques for greenhouse gas mitigation, precursors and gaseous pollutants emitted by motor vehicles. The efficiency of Oxan_X zeolite adsorption of gaseous emissions can assist in building low-cost efficient catalysts with fewer precious metals aggregates.